Mortalidade de blattella germanica (L., 1767) (Blattodea: Blattellidae) sob diferentes áreas e períodos de exposição a diferentes inseticidas - Parreira, Renata Souza [UNESP]; da Costa Ferreira, Marcelo [UNESP]; Martinelli, Nilza Maria [UNESP]; da Silva, Irene Cristina [UNESP]; Fernandes, Ana Paula [UNESP]; da Nóbrega Romani, Gustavo [UNESP] (My University, 2010)
The great importance of cockroaches as household pest have been on their ability to spread microorganisms harmful to humans and animals. Rest during the day in dark, humid and hot as sewerage. At night go into stores and kitchens or places to deposit and manipulation of food as bakeries, restaurants, hospitals and homes wich requires clinig operations. This work aimed to evaluate mortality of B. germanica (L., 1767) (Blattodea: Blattellidae) under different periods and exposure area treated by insecticides in laboratory. The tests were carried out at Department of Fitossanidade at UNESP, Campus of Jaboticabal, SP, Brasil. The insecticides were applied by Potter's tower sprayer on Petri dishes. Three times of exposure (2, 8 and 32 min) and four exposure areas (25, 50, 75 and 100%) and volume of 0,5 ml for the second experiment were tested. It was used the insecticides Pyrethroids gammacyalothrine, deltamethrine, lambdacialothrine, alfacipermethrine, cipermethrine and carbamates bendiocarb, in the dosages recommended by the manufacturers, and I was used control without application. Five adult cockroaches was confined in the dishes for both experiments. The mortality evaluation was done 0, 1, 2, 4, 24, 48 and 72 hours after of the confinement on the treated surface. It was concluded that for exposure duration experiment all the insecticides have a good efficiency. The exposure area experiment the insecticide cipermethrine was what the one which had the higher mortality. Regarding to the effect of exposure duration on the accumulated mortality every duration times had a high mortality. In relation to the exposure area the highest mortality reached to 100% of treated area.
Mortality of blatella germanica under different exposure area and duration to insecticides
Keywords: German cockroach; Handling of urban pest; Spraying technology; Urban Pest Management